2013
DOI: 10.3892/ol.2013.1251
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs in esophageal cancer tissue

Abstract: The aim of this study was to explore the association of specific microRNAs (miRNAs) with the development of esophageal cancer (EC) and to identify new molecular markers for EC by analyzing the expression profiles of miRNAs in EC tissues. The expression profiles of miRNAs in paired EC and paracancerous normal tissues were detected and bioinformatically analyzed using miRNA assays. The outcomes were validated using real-time polymerase chain reaction. The miRNA assays revealed a total of 60 differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 15 publications
0
79
0
Order By: Relevance
“…By contrast, it was suggested that miR-194 served a role in the promotion and progression of breast cancer (9) and pancreatic ductal adenocarcinoma (40). These studies indicated that miR-194 had various target genes (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Previous studies have demonstrated that miR-194 inhibited cell migration and invasion, which may have contributed to the anti-tumor activity of trastuzumab on HER2-overexpressing breast cancer cells (41,42).…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, it was suggested that miR-194 served a role in the promotion and progression of breast cancer (9) and pancreatic ductal adenocarcinoma (40). These studies indicated that miR-194 had various target genes (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Previous studies have demonstrated that miR-194 inhibited cell migration and invasion, which may have contributed to the anti-tumor activity of trastuzumab on HER2-overexpressing breast cancer cells (41,42).…”
Section: Discussionmentioning
confidence: 89%
“…Deregulated miR-28 expression has been observed in several types of cancer, including up-regulation in esophageal, cervical, and renal cancer, and in myeloproliferative malignancies and down-regulation in colorectal cancer and nasal-type natural killer/T-cell lymphoma (10)(11)(12)(13)(14)(15)(16). These apparently inconsistent observations are not surprising because it is well established that miRNAs can act both as tumor suppressors and oncogenes depending on the cell context (29).…”
Section: Mir-28 As a Candidate Tumor Suppressor In Gc-derived Lymphomasmentioning
confidence: 88%
“…miR-28 has been shown to be deregulated in several cancer types. Although increased levels of miR-28 expression have been observed in esophageal, cervical, renal cancer, as well as in the platelets of a fraction of myeloproliferative neoplasm patients (10)(11)(12)(13), miR-28 is down-regulated in colorectal cancer cells and nasal-type natural killer/T-cell lymphoma. In both these latter cell types, reexpression of miR-28 leads to reduced proliferation in cell lines (14)(15)(16).…”
mentioning
confidence: 99%
“…In addition, miR-452 decreased cyclin-dependent kinase inhibitor 1B (CDKN1B) mRNA and protein expression by directly targeting the 3'UTR of CDKN1B; the knockdown of CDKN1B resembled the phenotype resulting from overexpression of miR-452 expression (18). miR-452 was also demonstrated to be an oncogene in esophageal cancer (26) and urothelial carcinoma (27). These conflicting studies indicated that the expression and functions of miR-452 in human cancers have tissue specificity.…”
Section: Discussionmentioning
confidence: 99%